2016
DOI: 10.5296/jse.v7i1.10397
|View full text |Cite
|
Sign up to set email alerts
|

Demography Factors and Faculty Members’ Teaching Efficacy in Vietnamese Higher Education

Abstract: Faculty members' perceptions of teaching efficacy have a positive influence on teaching performance and students' learning achievement. Even less is known about university faculty teaching efficacy in the countries like Vietnam. This study was to investigate university faculties' perceptions of teaching efficacy in Vietnamese higher education and their relation to faculty members' demography. A questionnaire measuring 27 items of six factors of teaching efficacy was distributed to 124 university faculty member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Teaching efficacy of faculty members in higher education has a positive influence on teaching performance and students' learning achievement (Duong, Nguyen, & Nguyen, 2017).…”
Section: Teacher Efficacymentioning
confidence: 99%
“…Teaching efficacy of faculty members in higher education has a positive influence on teaching performance and students' learning achievement (Duong, Nguyen, & Nguyen, 2017).…”
Section: Teacher Efficacymentioning
confidence: 99%
“…Therefore, the consideration of the conditions in each region and each province, especially in the remote and mountainous areas, and their own characteristics such as the distance between schools and home, and the number of the children per class were not the same. This was not to be mentioned in the large cities, the parents' demand on the primary education had been raised (Duong, Nguyen & Nguyen, (2017), so the above amount of teacher redundancy could be un-significantly explained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the redundant teachers were solved rightly from the first year, the following years would become easy. However, it was easy to see the situation that primary school teachers quitted their jobs was quite significant (Attfield & Vu, 2013) due to the failure control of the post-training employment rate of the intermediate schools or the pedagogical departments of the universities to confirm the right situation of the post-training labor use (Duong et al, 2017). Therefore, it was necessary to have deep analysis to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of the relationship between male and female faculty teaching efficacy and educational attainment item of individual factor are very few in order to discuss with the results of this study. The research of Duong, Nguyen and Nguyen (2017) showed that there were statistical difference between these educational attainment and faculty teaching efficacy in technology usage factor (F = 5.009, p < 0.01). The finding post hoc comparison showed that faculty members holding bachelors' degree (M = 4.32, SD = 0.37) have higher scores in technology usage than those holding masters' degree (M = 3.88, SD = 0.61).…”
Section: Comparison Among Male and Female Faculty Teaching Efficacy Wmentioning
confidence: 99%